Effect of nano-calcium carbonate on resistance to calcium leaching and chloride penetration in recycled concrete - Jian-Hua Jiang; Si-Qi Zhao; Xiao-Zhe Shi; Rui-Qi Xia; Huang-Xin Zhang (European Journal of Environmental and Civil Engineering, 2026)

Polystyrene nanoparticles impair endometrial decidualization in early pregnant mice via oxidative stress-driven autophagy suppression and ferroptosis induction - Li-Qing Wang; Qian-Feng Qiao; Huang-Nian You; Yi-bin Zheng; Xiao-Mei Wu; Wen-Jie Yu; Zeng Liu; Wen-Juan Song; Lin-Hong Zhang; Jia-Rui Hu; Xin-Yu Mao; Yong-Jiang Zhou (Food and Chemical Toxicology, 2026)

Photoelectrochemical CO2 reduction toward ethanol on silicon-based photocathodes with Cu-Cu2O and TCPPCu MOF heterointerface - Xin Li; Rui Chen; Ying Li; Jie Huang; Haiyan Zhu; Gang Shi (Chemical Engineering Journal, 2026)

Oxygen-vacancy-mediated BrO3− electroreduction: Positively charged microenvironment enables directional diffusion and spontaneous adsorption - Xiangbin Huang; Yue Cheng; Zhipeng Luo; Ruiqi Zheng; Yangying Zhao; Salman Farissi; Rui Liu; Gong Zhang; Xin Yu; Huabin Zeng (Chemical Engineering Journal, 2026)

Transparent, bio-based dielectric films with ultrahigh breakdown strength fabricated from hydrogen-bonded cellulose acetate and tannic acid for energy storage - Rui Luo; Xin-rui Xiao; Zhe-hao Kang; Chao-qun Wu; Ting Huang; Nan Zhang; Yong Wang (Carbohydrate Polymers, 2026)

Bionic snail-shell-shaped evaporator featuring silver-nanoparticle-decorated carbon nanotubes for efficient solar desalination - Yutao Huang; Zhihong Chen; Xuan Wang; Xin Guan; Jia Zeng; Rui Li; Leitao Han (Chemical Engineering Journal, 2026)

Effect of the thickness of overlying soil on the location of trailing edge cracks in soil–bedrock landslides induced by water softening - Yun-kang Rao; Jia-xin Chang; Hai-ying Fu; Tao Yang; Huai-lin Chen; Zhe Zhang; Yi Yang; Rui Huang (Bulletin of Engineering Geology and the Environment, 2026)

Optimal basal-to-topdressing nitrogen ratios promote soil c-n coupling through microbial community modulation across loam and clay loam soils of North China Plain cropland - Jingyu Li; Yanqun Wang; Bin Wang; Rui Hou; Wenchao Zhen; Yuanyuan Huang; Yufei Liu; Xuguang Li; Zhengping Peng; Xin Fu (Applied Soil Ecology, 2026)

Aeolian transport of evaporite minerals in Utopia Planitia: insights from Qaidam Basin spectral analogs - Jianxun Shen; Honglei Lin; Zhaopeng Chen; Xue Guo; Yuqi Wang; Yizhong Zhang; Li Liu; Chengxiang Huang; Enze Wang; Rui Chang; Xuesen Xu; Zhicheng Cui; et al. (Science Bulletin, 2026)

Improving spatiotemporal assessment of watershed soil redistribution by integrating source-sink theory into a multi-model framework - Rui Tan; Yu Tao; Geng Guo; Kaiwen Huang; Zicheng Liu; Lin Chen; Xin Liu; Jie Lin (Journal of Hydrology, 2026)

CWN-Net: a precise segmentation model for composite water networks using multi-source and multi-temporal remote sensing imagery - Mingyang Li; Huimin Lei; Fulin Li; Jiwen Huang; Yuzhi Shi; Shangjie Xu; Han Wang; Sinan Wang; Rui Wang; Lili Liu; Suzhen Cheng; Lei Guo; et al. (Journal of Hydrology, 2026)

MFN2-mediated remodelling of ER-mitochondria communication alleviates ochratoxin A-induced hepatocyte ferroptosis by enhancing mitophagy - Zi-Yan Hu; Rui-Qi Liu; Yu-Xuan Ouyang; Ming-Shan Chen; Jia-Xin Wang; Ming Lou; Yi-Feng Huang; Hong-Li Si; Fu-Wei Jiang; Zhuo-Yu Liu; Yi-Bo Wang; Li Wang; et al. (Journal of Hazardous Materials, 2026)

PRISM: Turning prediction uncertainty into cost-effective management decisions for cadmium-contaminated rice - Ziqian Zhong; Qihong Zhu; Xinliang Liu; Shufang Pan; Lei Luo; Xin Luo; Hanhua Zhu; Rui Liu; Lin Zou; Daoyou Huang (Journal of Hazardous Materials, 2026)

Optimizing pe+pH via integrated water management and phosphorus fertilization enhances phytoextraction of Cd/As by rice plant in contaminated paddy soils - Rui Huang; Yunhe Xie; Xin Wang; Wei Wei; Bingyu Li; Jingmin Yang; Haoyu Chen; Saihua Liu; Xionghui Ji (Journal of Environmental Sciences, 2026)

Acute Stress Drives Adaptive Anxiety via Excitatory-Inhibitory Imbalance in the Prefrontal-Amygdala Circuit in Male Mice - Jia-Xin Zou; En Cao; Zhi-Hao Wang; Rui Han; Xing-Yan Lu; Cheng-Yuan Huang; Xia Qin; Wei-Zhu Liu; Wen-Hua Zhang; Bing-Xing Pan (Neuroscience Bulletin, 2026)

From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

Pancancer pro-angiogenic atlas unravels tumor-educated pericyte-augmented anti-angiogenic resistance - Yongqiang Zheng; Hui Sun; Zhe Fu; Haojie Chen; Guangyao Cai; Xin Huang; Yi-Qian Pan; Kai Yu; Ping Chen; Zhuoran Liang; Junteng Li; Jiamin Hu; et al. (Science Bulletin, 2026)

Invasive giant African snails as potential reservoirs of antimicrobial resistance and bacterial pathogens in urban park - Yiyue Zhang; Zhonghui Tang; Huayuan Shangguan; Rui Zhu; An Xie; Qiansheng Huang; Jianqiang Su; Patrick O'Connor; Yong Jiang; Xin Sun (Journal of Environmental Management, 2026)

Polyvinylpyrrolidone-enhanced terahertz metamaterials for room-temperature, trace VOC detection and discrimination - Rui Zhang; Lanju Liang; Xin Yan; Guifang Wu; Haiyun Yao; Zhenhua Li; Xiaofei Hu; Ziqun Wang; Zhaoqing Sun; Jie Huang (Chemical Engineering Journal, 2026)

Exposure to per- and polyfluoroalkyl substances and risk of reproductive system cancers: A systematic review and meta-analysis - Xin Liu; Zhihong Lv; Zixiang Huang; Rui Sun; Dingyu Zhu; Pengcheng Xu; Yiquan Xiong; Xiaowei Guo; Yaxuan Ren; Junhua Zhou (Journal of Environmental Health Science and Engineering, 2026)

Physicochemical properties, antioxidant activity, antibacterial properties, and fruit preservation potential of black soldier fly chitosan films - Bin-Qiao Yuan; Ting-Hao Yu; Jun-Kui Huang; Xin-Rui Ren; Run-Jia Wang; Guo-Xin Huang; Nortoji A. Khujamshukurov; Da-Wei Huang; Jin-Hua Xiao (Food Bioscience, 2026)

Cell-specific gene expression plasticity in response to hypoxia promotes high-altitude adaptive evolution - Wen-Tian Wei; Ze Yan; Hui Wu; Ming-Liang Zhou; Dong-Xin Mo; Xing Wan; Rui Ma; Mei-Ming Wu; Jia-Hui Huang; Ya-Jing Liu; Ji Yang; Meng-Hua Li (Science China Life Sciences, 2026)

Hydrothermal-responsive plasmonic aerogel for dynamic 3D hotspot regulation and ultrasensitive SERS detection of dairy products contaminants - Jing-Xiang Wang; Zhi-Gao Xu; Xin-Rui Wang; Yao-Yao Zhang; Ri-Hui Su; Xin-Xin Zhang; Su-Ming Dai; Wei-Wei Zhu; Xue-Cai Tan; Ke-Jing Huang; Jun Yan (Analytica Chimica Acta, 2026)

Algal ecological dynamics tracking model for studying hydrodynamic impacts on algae transport and accumulation in a shallow lake - Fei Du; Xiaobo Liu; Shiyan Wang; Chang Liu; Aiping Huang; Weijie Wang; Budong Li; Rui Gao; Xin Tian; Zhen Han; Hao Fan; Bi Wu (Journal of Hydrology, 2026)

Curcumin-derived smart anti-corrosion coating for early damage warning and active protection in diverse lighting and corrosive environments - Jinke Wang; Xin Guo; Congshu Huang; Danni Shang; Zhibin Chen; Rui Tian; Lingwei Ma; Dawei Zhang (Chemical Engineering Journal, 2026)

Urbanization exacerbates riverine greenhouse gas (CO2, CH4, N2O) emissions on the Qinghai-Tibet Plateau - Yuwei Huang; Bangguo Wang; Shengying Ye; Queping Yang; Rui Xu; Jian Ma; Qinping Song; Philip K. Hopke; Yuejun He; Xin Zhang; Lijing Wang; Yuanxun Zhang (Journal of Environmental Management, 2026)

Large-scale REE mineralization linked to intensive evolution of carbonatitic-alkaline magmas to brine-melts: Insights from Sr-Nd-Ba isotopes - Xiao-Chun Li; Geng-Xin Deng; Xiao-Yun Nan; Xue-Yin Yuan; Hong-Rui Fan; Fang Huang (Geochemistry, 2026)

Enhancing rice yield and nitrogen use efficiency through OsRAV1 expression and crop management - Yingbo Gao; Haiyan Chao; Xinyi Zhao; Xin Liu; Chang Liu; Guanda Hu; Xueqin Chen; Guowei Wang; Dunliang Wang; Rui Li; Juan Zhou; Xiaoxiang Zhang; et al. (Field Crops Research, 2026)

A co-delivery nanoplatform for coordinated STING activation and dual PI3K/COX-2 blockade potentiates Cancer immunotherapy - Zhe Zhang; Ruibai Chang; Jindian Fan; Bingjing Liang; Long Zheng; Rui Fan; Xin Huang; Yitong Wang; Jingyi Lv; Xiaoting Yang; Belal Abdellah; Khaled A.M. Abouzid; et al. (Chemical Engineering Journal, 2026)

A novel electrostatic-assisted airflow pollination end-effector for kiwifruit flowers with optimized charging and spraying parameters - Yusong Ding; Leilei He; Juncai Huang; Xin Wei; Yufei Shi; Hin Lim; Spyros Fountas; Shaojin Wang; Rui Li; Longsheng Fu (Computers and Electronics in Agriculture, 2026)

Quantifying the impact of vegetation greenness change on surface urban heat islands across 133 major cities of China - Rui Yao; Zhihao Zhang; Wenjie Li; Hao Li; Shiya Zhu; Hongji Zhu; Chuan Wang; Dewei Luo; Ying Yang; Junli Li; Weitao Han; Xin Huang (Environmental Research, 2026)

Defect passivation with Pb for high-performance Sb2S3 solar cells via vapor transport deposition - Gan Huang; Xin-Yi Cai; Hu Li; Jin-Rui Cai; Ying-Sen Xia; Zhi-Ping Huang; Li-Mei Lin; Fu-Bao Gong; Shui-Yuan Chen; Gui-Lin Chen (Chemical Engineering Journal, 2026)

Tree of life and conservation of gymnosperms in China - Chang-Wang Ma; Dan Xie; Hong Du; Kai-Yuan Huang; Yuan-Yuan Feng; Zhou-Rui Wei; Xin-Quan Liu; Cheng-Ru Li; Jing-Jing Sun; Xiao-Xin Wei; Zhi-Heng Wang; Wei-Hua Xu; et al. (Science China Life Sciences, 2026)

Sevoflurane-induced ferroptosis in developing neurons mediated by the NCOA4-ferritinophagy-GPX4 pathway - Cheng-Yi Lao; Wei-Xin Dai; Jie-Chao Zhou; Rui-Ping Huang; Huan Feng (Journal of Molecular Histology, 2026)

Heavy Metal Pollution Characteristics and Health Risk Assessment of Water Environment in Metal Mining Areas of the Han River Basin, Shaanxi Province - Longhao Huang; Yanmei Yang; Peng Zhang; Rui Meng; Xin Zhou; Qiang Zhou; Liansheng He; Zhihao Ye (Bulletin of Environmental Contamination and Toxicology, 2026)

Cloning, heterologus expression and characterization of a thermophilic and salt tolerant GH11 xylanase from Allostreptomyces psammosilenae YIM DR4008T - Xin-Wei Li; Dan Zhu; Lei Li; Run-Feng Yang; Shi-Yuan Fan; Zhi-Hua Lv; Meng-Di Rao; Rong-Huang Song; Peng Sang; Yi-Rui Yin; Li-Quan Yang (Antonie van Leeuwenhoek, 2026)

Release kinetics and bioaccessibility of heavy metal from antifouling paint particles in simulated digestive fluids: An emerging threat to marine biota - Zhen-Liang Li; Ting-Ting Xu; Shan-Shan Yao; Heng-Xiang Li; Shan Liu; Rui Hou; Lang Lin; Zhi-Xin Ni; Qun Xie; Xiao-Ping Huang; Xiang-Rong Xu (Marine Pollution Bulletin, 2025)

Ecological functions coupled with plasmid and phage-mediated dissemination drive the global prevalence of high-risk antimicrobial resistance genes in influent - Fang Huang; Shu-Hong Gao; Yanmei Zhao; Qi Liu; Rui Gao; Zihan Dai; Jingni Xie; Bin Liang; Jinsong Liang; Lu Fan; Xin Li; Ai-Jie Wang (Water Research, 2025)

Dual mechanisms of Vitisin A in managing alcoholic liver disease: Inhibition of lipogenesis and complement activation - Yuanqin Zhu; Huilin Deng; Jia Liu; Xusheng Li; Xin Huang; Zhaodi Che; Weibin Bai; Rui Jiao (Food and Chemical Toxicology, 2025)

Peripheral inflammation in spinocerebellar ataxia type 3: associations with genetic and clinical manifestations - Jia-Yi Zhang; Qiu-Ni Su; Han Lin; Wei Lin; Mao-Lin Cui; Zhuo-Ying Huang; Bei-Ning Ye; Ying-Xin Ye; Yi-Lin Jia; Qing-Ying Zhu; Zhi-Han Li; Min-Ting Lin; et al. (Inflammation Research, 2025)

Application of ambient noise tomography to coastal granite islands: A case study of Wuzhizhou Island in Hainan, China - Cheng Huang; Sheng Liu; Jun-Qiao Long; Chang-Rong Zhang; Bo Xiao; Da-Cheng Wang; Cheng-Long Wei; Rui Wang; Li Yan; Xuan Hu; Zhuo Xin; Xiu-Ji Meng; et al. (Applied Geophysics, 2025)

An energy-constrained profile parameterization of shear-driven turbulence in the interior ocean - Lei Lu; Chuanyu Liu; Rui Xin Huang; Fan Wang (Frontiers in Marine Science, 2025)
This paper proposes an energy-constrained profile parameterization of both turbulent kinetic energy dissipation rate ( ϵ ) and vertical diffusivity ( κ ), for shear instability-induced turbulence that is initiated in an initial unstable layer (IUL) where the gradient Richardson number R i ∈ ( 0 , 0.25 ) . Large-eddy simulation (LES) experiments provide the data of turbulent processes originating from Kelvin-Helmholtz instability of varied initial shear conditions. The energy-constrained framework posits ϵ and κ as proportional to K a and τ – 1 , where K a represents available kinetic energy, measuring the released kinetic energy, τ denotes turbulence evolution timescale. Both are determinable by the thickness of IUL ( h 0 ), buoyancy frequency ( N 0 ), vertical shear ( S 0 ), and Richardson number ( R i 0 ) of the IUL. Notably, unlike conventional schemes that parameterize turbulent mixing for single model grid point layer by layer, the present scheme parameterizes the turbulent mixing not only for the grid point(s) of IUL, but also for all the model grid points that are within a determined vertical turbulent penetration layer, by providing a profile of diffusivity. Therefore, the scheme is termed the energy-constrained profile parameterization (EPP). EPP aligns well with the LES results and direct microstructure measurements, outperforming existing parameterizations.

Interfacial engineering of 0D/3D CeO2/BA nanoarchitectures for highly efficient and selective CO2 photo-reduction to CH4 based on full-spectrum solar-energy utilization - Rui Xu; Chonghai Deng; Chengchen Wang; Yibin Zhu; Yonghui Tong; Zheng Chen; Peipei Sun; LiLi Wang; Lei Yang; Xin Liang; Yiping Wu; Jing Huang; et al. (Chemical Engineering Journal, 2025)

Cinnamaldehyde enhanced starch/chitosan composite films: A one-pot engineered solution for extended fruit shelf life - Qingbo Yao; Yan Chen; Zhizhi Zhang; Weijian Chen; Rui Wang; Langhong Wang; Yanyan Huang; Fengsong Liu; Xin-An Zeng (Carbohydrate Polymers, 2025)

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

Macrophage cytoskeletal and immune responses to photoaged and gastrointestinal-transformed polylactic acid micro/nanoplastics with protein corona - Xuri Wu; Feng Tan; Han Zhang; Liping Huang; Yan Wang; Xin He; Rui Cai; Shumin Li (Journal of Hazardous Materials, 2025)

The interactions, impacts, and removal strategies of microplastics (MPs) and antibiotic resistance genes (ARGs) in aquatic environments, particularly in wastewater treatment plants (WWTPs) - Ying Wang; Xin-Rui Zhang; Min-Min Qiang; Zheng Huang; Xin-Tao Liu; Run-Mei Li; Zi-Yue Li; Zai-Yong Zhang; Qian-Qian Zhang (Journal of Environmental Chemical Engineering, 2025)

Light-confining resonant metamaterial integrated with silicon-doped quantum dots for liquid-phase biomolecular detection - Rui Zhang; Jie Huang; Lanju Liang; Zhuyu Ding; Xin Yan; Guifang Wu; Haiyun Yao; Zhenhua Li; Xiaofei Hu; Ziqun Wang; Zhaoqing Sun (Chemical Engineering Journal, 2025)

Vapor additive strategy enabling perfect crystallization of vacuum-evaporated photovoltaic perovskites - Lei Huang; Zhang Chen; Kai-Li Wang; Zi-Hao Song; Xiao-Ying He; Zhen-Huang Su; Jing Chen; Chun-Hao Chen; Yu Xia; Yu-Tong Yang; Xin Chen; Rui-Hao Qin; et al. (Chemical Engineering Journal, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Associations Between Pre- and Post-Diagnosis Dietary Inflammatory Patterns and Ovarian Cancer Survival: Results From the Ovarian Cancer Follow-Up Study - Jia-Xin Liu; Rui-Han Bao; Meng Luan; Chuan Liu; Lang Wu; Fang-Hua Liu; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Qian Xiao; Dong-Hui Huang; Xiao-Ying Li; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Mitigation of arsenic uptake and accumulation in rice grains by applying husk-derived silicon in a synergistic way: Evidence from pot and field trials - Xianghong LI; Xin WANG; Xionghui JI; Jingmin YANG; Yunping YU; Rui HUANG; Bo PENG; Baoshan XING (Pedosphere, 2025)

Insights into ROL-driven and ROS-mediated metalloid oxidation and sequestration in the soil-rice iron barrier system - Jing-Min Yang; Xin Wang; Dong-Xing Guan; Rui Huang; Xiong-Hui Ji; Yun-He Xie; Bo Peng; Qin-Bo Qin (Journal of Hazardous Materials, 2025)

Palmitic acid triggers rhizosphere acidification to facilitate microbial nitrogen fixation: A perspective for phytoremediation of desertification alpine grassland via artificial root exudation mimicking - Fei Yan; Qian Huang; Dongming Chen; Xin Zheng; Rui Yin; Kangqi Zhang; Yan Lu; Yanfu Bai; Feida Sun; Jiqiong Zhou; Zhouwen Ma; Geng Sun; et al. (Journal of Environmental Management, 2025)

Recyclable flame retardant, luminescent, and transparent thermoplastic polyurethanes: applications in light conversion films for flexible solar cells - Li-Wei Su; Ming-Hao Liu; Yang Jing; Peng-Yu Huang; Bo Jiang; Rui-Guang Xing; Xin Ge; Ya-Hui Li; Jin-Xiao Bao; Gao-Fei Pan (Chemical Engineering Journal, 2025)

Development of recyclable polyvinyl alcohol-based transparent films with enhanced UV shielding for sustainable fruit preservation packaging - Xiaoli Liu; Tianyu Sun; Xiaoqing Wang; Rui Huang; Xuanxuan Huang; Xin Li; Zhanhui Lu (Food Packaging and Shelf Life, 2025)

Rapeseed transcription factor BnaC9bHLH35 promotes root growth and improves nitrogen use efficiency under low nitrate conditions - Qin-Xin Fang; Haokun Cheng; Zhongni Ma; Qiuyan Xu; Huanpeng Wang; Yunru Yan; Mengting Sun; Rui Wang; Wenlong Liu; Saeed Ullah; Yuhang Fan; Chunchun Huang; et al. (Theoretical and Applied Genetics, 2025)

Macoligophones A–I, prenylated acetophenone dimers and monomers from Maclurodendron oligophlebium - Jing-Jing Qi; Yu-Nan Qian; Ying Li; Xiang-Yu Liu; Rui-Yao Fu; Zheng-Hui Huang; Jian-Min Yue; Jin-Xin Zhao (Phytochemistry, 2025)

Versatile Dual-Emissive Boron-Nitrogen Co-Doped carbon Dots: Unlocking efficient electroluminescent Light-Emitting diodes with breakthrough EQE Approaching 7% - Ming-Zhu Li; Hong-Ji Tan; Qi-Rui Liang; Jie-Rong Yu; Peng Huang; Xiao-Qi Lai; Chun-Fa Wen; Chun-Sing Lee; Qing-Xiao Tong; Jing-Xin Jian (Chemical Engineering Journal, 2025)

The application of marine bioactive composite materials in environmental remediation - Yanan Huang; Hao Li; Ronglian Xing; Xiaorui Chen; Yuxin Sun; Meichen Tian; Ran Zhang; Xin Wang; Xinxin Wang; Rui Li; Lihong Chen; Hongxia Zhang; et al. (Desalination, 2025)

A comprehensive review on selenium and blood pressure: Recent advances and research perspectives - Pusong Tang; Rui Huang; Xing Zhong; Xin Chen; Yuhua Lei (Journal of Trace Elements in Medicine and Biology, 2025)

Selective preparation of aromatic compounds from catalytic pyrolysis polyester coating over Ni, Mo and Co metal modified ZSM-5 - Zhen-Qiang Yu; Yao-Xin Xiao; Dong Liang; Che Zhao; Zhen Huang; Gang-Qi Cheng; Rui Shan; Hao-Ran Yuan; Yong Chen (Journal of Environmental Chemical Engineering, 2025)

Geochemical constraints on the link between lunar magma ocean cumulates and the source of Chang'E-5 basalts from olivine trace element abundances - Yong Wu; Jie-Jun Jing; Zi-Ying Li; Ming-Kuan Qin; Ben-Xun Su; Jun Zhong; Dong-Fa Guo; Guang Fan; Rui-Ping Liu; Sheng He; Ting Li; Xiang-Kun Ge; et al. (Icarus, 2025)

Urinary concentrations of phthalate metabolites and the survival of high-grade serous ovarian cancer with advanced stage - Wen-Rui Zheng; Yi-Zi Li; Jin Xu; Ke-Xin Liu; Fang-Hua Liu; Wei-Yi Xing; Jia-Xin Liu; Lang Wu; Xiao-Ying Li; Dong-Hui Huang; Ting-Ting Gong; Qi-Jun Wu (Environmental Pollution, 2025)

P2/O3 biphasic Fe/Mn based cathodes for simultaneously realizing kinetic-enhancement and air-stabilization - Rui Huang; Shaohua Luo; Qi Sun; Lixiong Qian; Xin Liu; Shengxue Yan (Chemical Engineering Journal, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Identifying spatial drivers of soil heavy metal pollution risk integrating positive matrix factorization, machine learning, and multi-scale geographically weighted regression - Yujie Pan; Anmeng Sha; Wenjing Han; Chang Liu; Guowangchen Liu; Emily Welsch; Min Zeng; Shasha Xu; Yi Zhao; Shang Tian; Yiyi Li; Rui Deng; et al. (Journal of Hazardous Materials, 2025)

Development of starch-based films with enhanced hydrophobicity and antimicrobial activity by incorporating alkyl ketene dimers and chitosan for mango preservation - Yanyan Huang; Qingbo Yao; Rui Wang; Langhong Wang; Jian Li; Boru Chen; Fengsong Liu; Xin-An Zeng (Food Chemistry, 2025)

Exploration of the regulatory mechanism of pulsed electric field on the aggregation behavior of soybean protein isolates - Rui Wang; Pei-Feng Guo; Jin-Peng Yang; Yan-Yan Huang; Lang-Hong Wang; Jian Li; Song-Yi Lin; Qing-Lin Sheng; Xin-An Zeng; Yong-Xin Teng (Food Hydrocolloids, 2025)

The Impact of Different Mating Systems on Locomotion in Drosophila melanogaster - Rui Han; Jun Zhang; Ruo-Xi Wang; Jia-Xin Xu; Kai-Chen Weng; An-Xin Wang; Hao Huang; Yu-Yuan Lu; Yi-Jie Chen; Yu-Chen Wang (Journal of Insect Behavior, 2025)

Toward safe rice production in As-Cd co-contaminated paddy soils: Biogeochemical mechanisms and remediation strategies - Jing-Min Yang; Hui-Lin Chen; Xin Wang; Dong-Xing Guan; Xiong-Hui Ji; Yun-He Xie; Rui Huang; Bo Peng; Qin-Bo Qin (Critical Reviews in Environmental Science and Technology, 2025)

Evidence of sewage discharge on the coalescence mechanism of aquatic microbial communities during high amplitude hydrological periods - Xin Kou; Shier Huang; Rui Bian; Qingwen Tang; Hui Wang; Song Liu; Li Wang; Weixiao Qi; Xiaofeng Cao; Huachun Lan; Huijuan Liu; Jiuhui Qu (Science of The Total Environment, 2025)

A stab-/solvent-resistant HAG/silicone armor for durably stretchable electroluminescent device - Jun-Yue Li; Xin-Kai Qian; Qi-Ye Wang; Hong-Chao Sun; Xiu-Juan Li; Zhen-Yu Zhang; Chao-Ran Huang; Rui Guo; Fei Xiu; Ju-Qing Liu (Chemical Engineering Journal, 2025)

ZnCur nanoparticle-enhanced multifunctional hydrogel platform: Synergistic antibacterial and immunoregulatory effects for infected diabetic wound healing - Yan-Wen Ding; Zhi-Wei Zhang; Xin-Yu Cui; Rui-Yang Hu; Yang Li; Si-Da Huang; Si-Qi Du; Jin-Wei Dao; Dai-Xu Wei (Chemical Engineering Journal, 2025)

Analysis of Toxic Elements Pollution Sources and Crop Health Risks in Soil of Typical Thallium Mining Area - Zhihao Ye; Yanmei Yang; Qiang Zhou; Xin Zhou; Liansheng He; Rui Meng; Longhao Huang (Archives of Environmental Contamination and Toxicology, 2025)

Construction of a triple-mode sensing platform for effective differentiation, speciation, and monitoring of mercury and methylmercury bioaccumulation in crayfish via cation exchange reaction - Yiman Wu; Jie Liu; Shuqi Li; Rui Jian; Xin Yuan; Ke Huang (Science of The Total Environment, 2024)

Iron-doped diesel exhaust early-in-life inhalation-induced cardiopulmonary toxicity in chicken embryo: Roles of ferroptosis and acyl hydrocarbon signaling - Siyi Wang; Xinxian Gong; Junhua Yuan; Jing Huang; Rui Zhao; Jing Ji; Meinan Wang; Xiaoyu Shi; Wenya Xin; Yuxu Zhong; Yuxin Zheng; Qixiao Jiang (Environmental Pollution, 2024)

T cell senescence may contribute to immunothrombosis via Th17 immune transition in COVID-19 - Wenxing Li; Rui Qian; Zhaoming Zhou; Lei Wen; Quan Yin; Xiang Zhou; Xiaowei Li; Jie Cheng; Xinlu Zhang; Xin Zeng; Zhuoya Wang; Yingying Huang; et al. (Science Bulletin, 2024)

Unveiling the synergism and reaction pathway of ethyl acetate removal in DBD/absorption integrated reactor - Li-qiang Qi; Lin Huang; Jia-yue Lei; Rui Dai; Fan Du; Bo Wang; Jing-xin Li; Feng Liu (Process Safety and Environmental Protection, 2024)

Mn vacancy engineering design of Fe/Mn based cathodes for breaking the spell between “sodium limiting” in air-stabilization and “sodium promoting” on kinetics - Rui Huang; Shaohua Luo; Qi Sun; Xin Yan; Haoran Zhang; Lixiong Qian; Xin Liu; Xingzhong Cao; Peng Zhang; Shengxue Yan (Chemical Engineering Journal, 2024)

The CYP3A inducer dexamethasone affects the pharmacokinetics of sunitinib by accelerating its metabolism in rats - Guang-rong Lu; Rui-zhen Wang; Xin-yu Zhao; Jun-er Xu; Cheng-ke Huang; Wei Sun; Rui-jie Chen; Zhe Wang (Chemico-Biological Interactions, 2024)

Shifts in reproductive strategies in the evolutionary trajectory of plant lineages - Xin-Jian Zhang; Xian-Han Huang; Jacob B. Landis; Quan-Sheng Fu; Jun-Tong Chen; Peng-Rui Luo; Li-Juan Li; Heng-Yi Lu; Hang Sun; Tao Deng (Science China Life Sciences, 2024)

Soil organic phosphorus is mainly hydrolyzed via phosphatases from ectomycorrhiza-associated bacteria rather than ectomycorrhizal fungi - Jing Yuan; Rui Yan; Xueqiong Zhang; Kai Su; Hui Liu; Xin Wei; Ran Wang; Lanlan Huang; Nianwu Tang; Shanping Wan; Wei Liu; Hans Lambers; et al. (Plant and Soil, 2024)

The presences of water in the generation of calc-alkaline I-type granitic magmas at continental arc: Insight from Neoproterozoic Ailaoshan magmatism at the southwestern margin of the Yangtze Block, South China - Bin Huang; Rui Li; Nimat Ullah Khattak; Xin-Yu Cai; Yang Zhang; Wei Wang (Precambrian Research, 2024)

Metabolomics combined with intestinal microbiota analysis to reveal the effects of Inonotus hispidus on chronic kidney disease caused by high-protein diet - Xin Pang; Zitao Guo; Long Ao; Yong Huang; Bo Hu; Zhenghua Gu; Yu Xin; Zhongpeng Guo; Rui Zhu; Moying Li; Liang Zhang (Food Bioscience, 2024)

An efficient Au/ZnO catalyst for the photocatalytic conversion of methane to formaldehyde - Yan-Qun Chen; Lei-Xin Mao; Rui-Xin Zhang; Xin-Yu Zhang; Zhi-Hua Gao; Lei Liu; Wei Huang; Zhi-Jun Zuo (Chemical Engineering Journal, 2024)

A Cysteinyl-tRNA Synthetase Mutation Causes Novel Autosomal-Dominant Inheritance of a Parkinsonism/Spinocerebellar-Ataxia Complex - Han-Kui Liu; Hong-Lin Hao; Hui You; Feng Feng; Xiu-Hong Qi; Xiao-Yan Huang; Bo Hou; Chang-Geng Tian; Han Wang; Huan-Ming Yang; Jian Wang; Rui Wu; et al. (Neuroscience Bulletin, 2024)
This study aimed to identify possible pathogenic genes in a 90-member family with a rare combination of multiple neurodegenerative disease phenotypes, which has not been depicted by the known neurodegenerative disease. We performed physical and neurological examinations with International Rating Scales to assess signs of ataxia, Parkinsonism, and cognitive function, as well as brain magnetic resonance imaging scans with seven sequences. We searched for co-segregations of abnormal repeat-expansion loci, pathogenic variants in known spinocerebellar ataxia-related genes, and novel rare mutations via whole-genome sequencing and linkage analysis. A rare co-segregating missense mutation in the CARS gene was validated by Sanger sequencing and the aminoacylation activity of mutant CARS was measured by spectrophotometric assay. This pedigree presented novel late-onset core characteristics including cerebellar ataxia, Parkinsonism, and pyramidal signs in all nine affected members. Brain magnetic resonance imaging showed cerebellar/pons atrophy, pontine-midline linear hyperintensity, decreased rCBF in the bilateral basal ganglia and cerebellar dentate nucleus, and hypo-intensities of the cerebellar dentate nuclei, basal ganglia, mesencephalic red nuclei, and substantia nigra, all of which suggested neurodegeneration. Whole-genome sequencing identified a novel pathogenic heterozygous mutation (E795V) in the CARS gene, meanwhile, exhibited none of the known repeat-expansions or point mutations in pathogenic genes. Remarkably, this CARS mutation causes a 20% decrease in aminoacylation activity to charge tRNA Cys with L-cysteine in protein synthesis compared with that of the wild type. All family members carrying a heterozygous mutation CARS (E795V) had the same clinical manifestations and neuropathological changes of Parkinsonism and spinocerebellar-ataxia. These findings identify novel pathogenesis of Parkinsonism-spinocerebellar ataxia and provide insights into its genetic architecture.

Effects of low-temperature stress on serum biochemical indicators, intestinal microbiome, and transcriptome of juvenile golden pompano (Trachinotus ovatus) - Rong-xin Li; Eric Amenyogbe; Yi Lu; Jing-hui Jin; Rui-tao Xie; Jian-sheng Huang (Aquaculture International, 2024)

Association of prenatal multiple metal exposures with child neurodevelopment at 3 years of age: A prospective birth cohort study - Yun Qiu; Yuxin Liu; Ming Gan; Weiting Wang; Tao Jiang; Yangqian Jiang; Hong Lv; Qun Lu; Rui Qin; Shiyao Tao; Lei Huang; Xin Xu; et al. (Science of The Total Environment, 2024)

Selective metallization of polymer based on nanoscale tungsten oxide laser activators for advanced electronics - Haoran Xu; Feifan Yu; Jin Feng; Rui Xu; Jiameng Huang; Jia-Xin Wang; Tao Zhou (Chemical Engineering Journal, 2024)

New approach for raw biogas: Production of single cell protein by sulfide-tolerant methane-oxidizing bacteria consortia - Hai-Ming Huang; Zhi-Xin Xue; Yu-Feng Jiang; Rui Li; Rong-Bo Guo; Xiao-Lei Fan; Shan-Fei Fu (Chemical Engineering Journal, 2024)

Mechanisms for carbon stock driving and scenario modeling in typical mountainous watersheds of northeastern China - Jin Zhang; Wen-Guang Zhang; Xin-Yan Zhang; Yu-Hong Li; Ming-Ming Feng; Peng Qi; Yi-Qiang Huang; Rui Li; Ming Jiang; Yuan-Chun Zou; Yi Wu (Environmental Monitoring and Assessment, 2024)

Computational tools for plant genomics and breeding - Hai Wang; Mengjiao Chen; Xin Wei; Rui Xia; Dong Pei; Xuehui Huang; Bin Han (Science China Life Sciences, 2024)

Effects of different cold chain logistics modes on the quality and bacterial community succession of fresh pork - Su Wang; Dequan Zhang; Qingfeng Yang; Xiangyuan Wen; Xin Li; Tongjing Yan; Rui Zhang; Wei Wang; Kumayl Hassan Akhtar; Caiyan Huang; Chengli Hou (Meat Science, 2024)

Phyllanthus emblica Linn: A comprehensive review of botany, traditional uses, phytonutrients, health benefits, quality markers, and applications - Qin-Ge Ma; Lei Wang; Rong-Hua Liu; Jin-Bin Yuan; Hui Xiao; Zhang-Yang Shen; Jia-Xin Li; Jia-Zeng Guo; Lan Cao; Hui-Lian Huang; Rong-Rui Wei (Food Chemistry, 2024)

Amorphous/Graphitic carbon phase engineering of Corrosion-Resistant Fe@C Core-Shell nanowires for optimized dipole polarization and enhanced microwave absorption - Ping-an Yang; Wenjiao Deng; Haibo Ruan; Zhengwei Qu; Rui Li; Lirui Wang; Jiufei Luo; Zhihao Zhou; Mengjie Shou; Xin Huang; Qiao Chen; Xinglong Gong (Chemical Engineering Journal, 2024)

Multi-omics Analysis of Volatile Flavor Components in Pacific Chub and Spanish Mackerel during Freezing using GC–MS–O - Yi-Zhen Huang; Yu Liu; Rui Zhu; Xiaoxiao Ma; Songlin Xin; Beiwei Zhu; Xiu-Ping Dong (Food Chemistry, 2024)

Highly sensitive detection of aflatoxin B1 byCRISPR/Cas12a-assisted single nanoparticle counting - Chengchao Zhang; Xin Zhao; Zili Huang; Ziyan Li; Jianyu Hu; Rui Liu; Yi Lv (Food Chemistry, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

Enhancing the effluent prediction accuracy with insufficient data based on transfer learning and LSTM algorithm in WWTPs - Yadan Yu; Yangwu Chen; Shunbo Huang; Rui Wang; Yadong Wu; Houzhen Zhou; Xin Li; Zhouliang Tan (Journal of Water Process Engineering, 2024)

Ecological impacts of the expansion of offshore wind farms on trophic level species of marine food chain - Lijing Wang; Bangguo Wang; Wenxi Cen; Rui Xu; Yuwei Huang; Xin Zhang; Yinghui Han; Yuanxun Zhang (Journal of Environmental Sciences, 2024)

Effects of pretension loads on bending behaviors of CFRP tendons - Zhen Wang; Rui Guo; Bin Hong; Guijun Xian; Meiyin Xin; Shengde Huang; Haijuan Shen (Engineering Structures, 2024)

Mechanisms of benzene and benzo[a]pyrene biodegradation in the individually and mixed contaminated soils - Mukhtiar Ali; Qing Wang; Zhuanxia Zhang; Xing Chen; Min Ma; Zhiwen Tang; Rui Li; Biao Tang; Zhongyuan Li; Xiangfeng Huang; Xin Song (Environmental Pollution, 2024)

A renal-targeted gene delivery system derived from spermidine for arginase-2 silencing and synergistic attenuation of drug-induced acute kidney injury - Xu-Rui Gu; Kun Liu; Yi-Xuan Deng; Bi-Xiao Xiang; Ling-Yun Zhou; Wen-Jun Yin; Jia-Xin Huang; Ying-Cai Meng; Dian-Ke Li; Rui-Man Que; Zhi-Yao Tang; Guang-Liang Zhou; et al. (Chemical Engineering Journal, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Effects of Fractionation Methods on Soil Aggregate Microbial Community Composition: Settling vs. Wet Sieving - Xin Gao; Rui Wang; Yaxian Hu; Weijia Li; Lanlan Du; Shengli Guo; Shengjun Wu; Ping Huang (Journal of Soil Science and Plant Nutrition, 2024)

Effects of short and long-term thermal exposure on microbial compositions in soils contaminated with mixed benzene and benzo[a]pyrene: A short communication - Mukhtiar Ali; Xin Song; Qing Wang; Zhuanxia Zhang; Meng Zhang; Min Ma; Jilu Che; Rui Li; Xing Chen; Zhiwen Tang; Biao Tang; Xiangfeng Huang (Science of The Total Environment, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Structurally diverse rearranged sesquiterpenoids, including a pair of rare tautomers, from the aerial parts of Daphne penicillata - Peng Zhao; Ben-Song Xin; Li Ye; Zhen-Tao Ma; Guo-Dong Yao; Rui Shi; Xia-Hong He; Bin Lin; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2024)

Estimation of the surface urban heat island intensity across 1031 global cities using the regression-modification-estimation (RME) method - Rui Yao; Xin Huang; Yongjun Zhang; Lunche Wang; Jiayi Li; Qiquan Yang (Journal of Cleaner Production, 2024)

Identification, characterization and hypolipidemic effect of novel peptides in protein hydrolysate from Protaetia brevitarsis larvae - Zong-Qi Zhang; Xin-Rui Ren; Jin Geng; Si-Cong Chen; Qing-Lei Wang; Chun-Qin Liu; Jin-Hua Xiao; Da-Wei Huang (Food Research International, 2024)

Identification and characterization of an L-type lectin from obscure puffer Takifugu obscurus in response to bacterial infection - Fu-Hui Jiang; Ying Huang; Xin-Yue Yu; Li-Fan Cui; Yan Shi; Xiao-Rui Song; Zhe Zhao (Fish & Shellfish Immunology, 2024)

Lipopolysaccharides from a Shiraia fruiting body-associated bacterium elicit host fungal hypocrellin A biosynthesis through nitric oxide generation - Xin Ping Li; Wen Hao Shen; Lu Lu Zhou; Qun Yan Huang; Rui Peng Cong; Li Ping Zheng; Jian Wen Wang (Carbohydrate Polymers, 2024)

Microalgae biofilm photobioreactor and its combined process for long-term stable treatment of high-saline wastewater achieved high pollutant removal efficiency - Gaozhong Fan; Jie Huang; Xin Jiang; Weile Meng; Rui Yang; Jinsong Guo; Fang Fang; Jixiang Yang (Journal of Environmental Chemical Engineering, 2023)

Bamboo polysaccharides elicit hypocrellin A biosynthesis of a bambusicolous fungus Shiraia sp. S9 - Wen Hao Shen; Lu Lu Zhou; Xin Ping Li; Rui Peng Cong; Qun Yan Huang; Li Ping Zheng; Jian Wen Wang (World Journal of Microbiology and Biotechnology, 2023)

A multi-view assisted registration network for MRI registration pre- and post-therapy - Yanxia Liu; Xiaozhen Li; Rui Li; SiJuan Huang; Xin Yang (Medical & Biological Engineering & Computing, 2023)

Enhanced As extraction from paddy soils with high As contamination risk by rice plant upon Si fertilization - Rui Huang; Xin Wang; Wei Wei; Yunhe Xie; Saihua Liu; Haoyu Chen; Renjie Zhang; Xionghui Ji (Chemosphere, 2023)

Rapid determination of the relative configuration of diverse 8,4′-oxyneolignans by NMR analysis: Retrospective studies, improvement and structural revision - Peng Zhao; Li-Li Lou; Ben-Song Xin; Zhi-Yuan Li; Rui Guo; Wei-Yu Zhou; Tian-Ming Lv; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2023)

Bimodal interferences of Pb(II) induced by parallel deposition in Pb(II)-Cu(II) electrochemical detections: Voltammetric signals analysis combined with numerical simulations on transient interfacial phenomena - Rui-Ze Xia; Xin Cai; Bo Liang; Hai-Hua Dai; Yang-Zhi Liu; Meng Yang; Shi-Hua Chen; Pei-Hua Li; Xing-Jiu Huang (Journal of Hazardous Materials, 2023)

mARC dependent NO synthesis activates CanA-Relish-AMPs signal pathway in Eriocheir sinensis during nitrite stress - Rui Jia; Liangmin Zheng; Lihua Zhang; Xin Huang; Qian Ren (Fish & Shellfish Immunology, 2023)

Revealing the solid-solution interface interference behaviors between Cu2+ and As(III) via partial peak area analysis of simulations and experiments - Bo Liang; Xiang-Yu Xiao; Zong-Yin Song; Yong-Yu Li; Xin Cai; Rui-Ze Xia; Shi-Hua Chen; Meng Yang; Pei-Hua Li; Chu-Hong Lin; Xing-Jiu Huang (Analytica Chimica Acta, 2023)

Association between PM2.5 exposure and the outcomes of ART treatment: A prospective birth cohort study - Yifan Wang; Yun Qiu; Bo Huang; Jiangbo Du; Liya Liu; Tao Jiang; Yangqian Jiang; Hong Lv; Qun Lu; Rui Qin; Shiyao Tao; Lei Huang; et al. (Science of The Total Environment, 2023)

Contrasting the effect of aerosol properties on the planetary boundary layer height in Beijing and Nanjing - Xin Huang; Yuying Wang; Yi Shang; Xiaorui Song; Rui Zhang; Yuxiang Wang; Zhanqing Li; Yuanjian Yang (Atmospheric Environment, 2023)

The extraordinarily large vortex structure of Typhoon In-fa (2021), observed by spaceborne microwave radiometer and synthetic aperture radar - Ziyao Sun; Lina Bai; Xuesong Zhu; Xin Huang; Rui Jin; Hui Yu; Jie Tang (Atmospheric Research, 2023)

Insights into the quantitative structure–activity relationship for ionic liquids: a bibliometric mapping analysis - Rui Huang; Hui Liu; Ze Wei; Yi Jiang; Kai Pan; Xin Wang; Jie Kong (Environmental Science and Pollution Research, 2023)

TRPC6 promotes daunorubicin-induced mitochondrial fission and cell death in rat cardiomyocytes with the involvement of ERK1/2-DRP1 activation - Li-Xia Xu; Rui-Xing Wang; Jian-Feng Jiang; Gao-Cheng Yi; Jin-Jin Chang; Rui-Lan He; Hai-Xia Jiao; Bin Zheng; Long-Xin Gui; Jun-Jin Lin; Zhi-Hong Huang; Mo-Jun Lin; et al. (Toxicology and Applied Pharmacology, 2023)

Comparative study of the combustion and kinetic characteristics of fresh and naturally aged pine wood - Jun Deng; Tong-shuang Liu; Min Yao; Xin Yi; Guang-Xing Bai; Qian-rui Huang; Zheng Li (Fuel, 2023)

Duox mediated ROS production inhibited WSSV replication in Eriocheir sinensis under short-term nitrite stress - Rui Jia; Xiaoling Dai; Yanfang Li; Xintong Yang; Xiuwen Min; Derun Quan; Peng Liu; Xin Huang; Jiachun Ge; Qian Ren (Aquatic Toxicology, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Groundwater table fluctuation: A driving force affecting nitrogen transformation in nitrate-contaminated groundwater - Rui Zuo; Shida Zheng; Xin Liu; Guanlan Wu; Shufang Wang; Jinsheng Wang; Jiawei Liu; Chenxi Huang; Yuanzheng Zhai (Journal of Hydrology, 2023)

Photo-assisted thermal catalysis for methanol synthesis from methane oxidation on Cu-MOR/g-C3N4 - Yan-Qun Chen; Rui-Xin Zhang; Miao Ren; Ya-Xin Jin; Wen-Jing Wang; Jia-Yao Feng; Zhi-Hua Gao; Zhi-Feng Yan; Yi-Ming Liu; Wei Huang; Lei Liu; Zhi-Jun Zuo (Fuel, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Thermodynamics and inhibition mechanism of imidazolium-based ionic liquids for inhibiting spontaneous combustion of iron sulfide - Hui Liu; Xiaoqing Gou; Kai Pan; Rui Huang; Zhihui Lang; Dong Ye; Xin Wang; Haining Wang (Fuel, 2023)

Global seamless and high-resolution temperature dataset (GSHTD), 2001–2020 - Rui Yao; Lunche Wang; Xin Huang; Qian Cao; Jing Wei; Panxing He; Shaoqiang Wang; Lizhe Wang (Remote Sensing of Environment, 2023)

High density mapping of wheat stripe rust resistance gene QYrXN3517-1BL using QTL mapping, BSE-Seq and candidate gene analysis - Shuo Huang; Yibo Zhang; Hui Ren; Xin Zhang; Rui Yu; Shengjie Liu; Qingdong Zeng; Qilin Wang; Fengping Yuan; Ravi P. Singh; Sridhar Bhavani; Jianhui Wu; et al. (Theoretical and Applied Genetics, 2023)

Effects of low-temperature stress on intestinal structure, enzyme activities and metabolomic analysis of juvenile golden pompano (Trachinotus ovatus) - Rong-xin Li; Eric Amenyogbe; Yi Lu; Jing-hui Jin; Rui-tao Xie; Jian-sheng Huang (Frontiers in Marine Science, 2023)
Water temperature plays a crucial role in the growth, survival, and reproduction of fish species, as they make up the majority of aquatic fauna. In this study, the effects of low temperature were studied on the functional state of juvenile golden pompano ( Trachinotus ovatus ) under low-temperature stress. The study was conducted at 28°C in the control group and 18°C in the cold group for 14 d to determine the intestinal tissue, digestive and antioxidant enzyme activities, and metabolites of juvenile fish. The results showed that: (1) the swelling degree of the muscle layer deepened and was congested with a longer low-temperature stress period. The folds were sparse, from slight swelling to shedding and deformation. The intestinal mucosa was necrotic and had vacuoles, and the number gradually increased. Serious erosion of the villi occurred. (2) The specific activities of digestive enzymes showed a downward trend. (3) The intestinal superoxide dismutase (SOD) activity, malondialdehyde (MDA) content, and glutathione peroxidase (GSH-Px) activity showed an upward trend. The intestinal catalase (CAT) activity showed a downward trend. (4) Compared with the control group, there were 28 metabolites in the cold group showing significant differences, among which Z, 11Z, 14Z-eicosatrienoic acid, stearic acid, and adrenic acid showed an upward trend. In contrast, spermidine and uracil showed a downward trend. Among the enriched metabolic pathways, the main differential pathways were unsaturated fatty acid biosynthesis, fatty acid biosynthesis, linoleic acid metabolism, pyrimidine metabolism, and β-alanine metabolism. According to metabolomic analysis, under low-temperature stress, the fish body improved the synthesis of unsaturated fatty acids and saturated fatty acids to adapt to a low-temperature environment and consumed spermidine to improve its immune ability to clear the peroxide generated by the synthesis of unsaturated fatty acids in the body so that the cells were protected from oxidative damage. After 14 days, low-temperature stress affected metabolites and enzyme activity indices in juvenile golden pompano. Low-temperature stress causes changes in intestinal antioxidants and digestive enzymes and damage intestinal tissues. As a result of this exploration of how low temperatures affect the juvenile golden pompano, the foundation is laid for future studies, such as the molecular mechanisms of low-temperature adaptation in fish species.

Thiobacillus spp. and Anaeromyxobacter spp. mediate arsenite oxidation-dependent biological nitrogen fixation in two contrasting types of arsenic-contaminated soils - Yongbin Li; Lifang Guo; Rui Yang; Zhaohui Yang; Haihan Zhang; Qiqian Li; Zhiguo Cao; Xin Zhang; Pin Gao; Wenlong Gao; Geng Yan; Duanyi Huang; et al. (Journal of Hazardous Materials, 2023)

Associations of co-exposure to polycyclic aromatic hydrocarbons and metals with hyperuricemia risk in Chinese coke oven workers: Mediating roles of oxidative damage - Chaofan Guo; Xin Liu; Xiaojing Liao; Haimei Wu; Zhaorui Zhang; Dehua Wu; Rui Ma; Yongshun Huang; Na Zhao; Yongmei Xiao; Qifei Deng (Environmental Pollution, 2023)

Receptor and Ionic Mechanism of Histamine on Mouse Dorsolateral Striatal Neurons - Jian-Ya Peng; Kang-Li Shen; Xiu-Juan Fan; Zeng-Xin Qi; Hui-Wei Huang; Jian-Lan Jiang; Jian-Hua Lu; Xiao-Qin Wang; Xiao-Xia Fang; Wang-Rui Yuan; Qiao-Xuan Deng; Shu Chen; et al. (Molecular Neurobiology, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Characterizing diversity based on phenotypes and molecular marker analyses of purple yam (Dioscorea alata L.) germplasm in southern China - Xin Chen; Jingyu Sun; Qianglong Zhu; Yao Xiao; Hongyu Zhang; Yingjin Huang; Putao Wang; Tianxu Cao; Rui Hu; Zijin Xiang; Nan Shan; Qinghong Zhou (Genetic Resources and Crop Evolution, 2022)

Compounding soils to improve cropland quality: A study based on field experiments and model simulations in the loess hilly-gully region, China - Yun-xin Huang; Zheng-jia Liu; Yan-sui Liu; Yu-rui Li; Xue-qi Liu (Journal of Mountain Science, 2022)

Changes in amino acid and fatty acid composition during early development in cobia (Rachycentron canadum) - Jian-sheng Huang; Rong-xin Li; Rui-tao Xie; You-ming Chen; Jian-dong Zhang; Eric Amenyogbe; Gang Chen (Frontiers in Marine Science, 2022)
An estimation of the utilization of endogenous nutrients from the yolk sac that occurs during embryonic and early larval development can be a valuable approach to studying the nutritional requirements of fish larvae. In this study, fertilized eggs, embryos (before the membrane, 24 hours after fertilization), newly-hatched larvae (0-d-old), and open-mouthed larvae (3-day-old, unfed rotifers) samples of cobia ( Rachycentron canadum ) were collected to determine the amino acid and fatty acid profiles. Crude protein composition varies significantly for cobia during the different stages of development. The total amino acids, except for lysine(Lys), histidine (His), methionine(Met), serine(Ser), and glycine(Gly), had no significant change in the early development stage ( P > 0.05); the content of other six essential amino acids (EAA) and six non-essential amino acids (NEAA) was consistent with the changing trend of total essential amino acid. From hatching newly hatched larvae to open-mouthed larvae, except for Leu, Phe and Ser, decreased significantly ( P <0.05). From the utilization rate of FAA, the utilization rate of Lys and Leu was the highest (60.26%) and (52.21%) in the embryonic and endogenous nutritional stages, respectively. The water content of the open-mouthed larvae of cobia was significantly higher than that of the fertilized eggs, embryos, and newly hatched larvae ( P < 0.05). Three kinds of saturated fatty acids (SFA), five kinds of monounsaturated fatty acids (MUFA), and eight kinds of polyunsaturated fatty acids (PUFA) were detected in the dry samples of each developmental stage. Based on these results, juvenile cobia can thrive with a wide range of crude protein concentrations. Further refinement of commercial cobia production feeds would have beneficial consequences for economic and environmental concerns due to the positive impacts of optimizing the protein component as well as the ability to maintain the rapid growth rates. The results show that the larval development of cobia needs to consume large amounts of n3PUFA (especially DHA and EPA) to improve the larvae’s survival rate. Research methods will always have limitations when evaluating the relationship between early life nutrition interventions and well-being outcomes later in life. This study provides essential information regarding cobia larvae’s fatty acid requirements.

Circulation in the South China Sea is in a state of forced oscillation: Results from a simple reduced gravity model with a closed boundary - Rui Xin Huang; Hui Zhou (Acta Oceanologica Sinica, 2022)

Dynamics of seasonal and interannual variability of the ocean bottom pressure in the Southern Ocean - Xiaoqin Xiong; Xuhua Cheng; Niansen Ou; Tao Feng; Jianhuang Qin; Xiao Chen; Rui Xin Huang (Acta Oceanologica Sinica, 2022)

Genomic molecular signatures determined characterization of Mycolicibacterium gossypii sp. nov., a fast-growing mycobacterial species isolated from cotton field soil - Rui-Rui Huang; Shen-Rong Yang; Cheng Zhen; Xian-Feng Ge; Xin-Kai Chen; Zhi-Qiang Wen; Ya-Nan Li; Wen-Zheng Liu (Antonie van Leeuwenhoek, 2021)

Elevated pCO2 Impedes Succession of Phytoplankton Community From Diatoms to Dinoflagellates Along With Increased Abundance of Viruses and Bacteria - Ruiping Huang; Jiazhen Sun; Yunlan Yang; Xiaowen Jiang; Zhen Wang; Xue Song; Tifeng Wang; Di Zhang; He Li; Xiangqi Yi; Shouchang Chen; Nanou Bao; et al. (Frontiers in Marine Science, 2021)
Eutrophic coastal regions are highly productive and greatly influenced by human activities. Primary production supporting the coastal ecosystems is supposed to be affected by progressive ocean acidification driven by increasing CO 2 emissions. In order to investigate the effects of high p CO 2 (HC) on eutrophic plankton community structure and ecological functions, we employed 9 mesocosms and carried out an experiment under ambient (∼410 ppmv) and future high (1000 ppmv) atmospheric p CO 2 conditions, using in situ plankton community in Wuyuan Bay, East China Sea. Our results showed that HC along with natural seawater temperature rise significantly boosted biomass of diatoms with decreased abundance of dinoflagellates in the late stage of the experiment, demonstrating that HC repressed the succession from diatoms to dinoflagellates, a phenomenon observed during algal blooms in the East China Sea. HC did not significantly influence the primary production or biogenic silica contents of the phytoplankton assemblages. However, the HC treatments increased the abundance of viruses and heterotrophic bacteria, reflecting a refueling of nutrients for phytoplankton growth from virus-mediated cell lysis and bacterial degradation of organic matters. Conclusively, our results suggest that increasing CO 2 concentrations can modulate plankton structure including the succession of phytoplankton community and the abundance of viruses and bacteria in eutrophic coastal waters, which may lead to altered biogeochemical cycles of carbon and nutrients.

Generation and identification of endothelial-specific Hrh2 knockout mice - Rui Meng; Wen-Ke Cai; Wen-Mang Xu; Qiang Feng; Ping Wang; Yan-hua Huang; Yu-Xin Fan; Tao Zhou; Qin Yang; Zhi-Ran Li; Gong-Hao He (Transgenic Research, 2021)

Rescue effects of Se-enriched rice on physiological and biochemical characteristics in cadmium poisoning mice - Yang Su; Ling Li; Muhammad Umer Farooq; Xin Huang; Tengda Zheng; Yu Jie Zhang; Hla Hla Ei; Faiz Hussain Panhwar; Zhichen Tang; Rui Zeng; Yuanke Liang; Xiaoying Ye; et al. (Environmental Science and Pollution Research, 2021)

Comparative Transcriptomic Analyses of Haemophilus parasuis Reveal Differently Expressed Genes among Strains with Different Virulence Degrees - Yuan Y. Zhou; Chao Wang; Jing Yuan; Rong L. Yin; Xin Chen; Rui Li; Xue L. Zhang; Jing Wang; Chen Huang; Rong H. Yin (Current Microbiology, 2021)

Development of global soil erosion research at the watershed scale: a bibliometric analysis of the past decade - Xuan Huang; Kai-Rui Wang; Yu-wen Zou; Xin-Chun Cao (Environmental Science and Pollution Research, 2021)

Risk factors and clinical characteristics of tacrolimus-induced acute nephrotoxicity in children with nephrotic syndrome: a retrospective case-control study - Ping Gao; Xin-Lei Guan; Rui Huang; Xiao-Fang Shang-guan; Jiang-Wei Luan; Mao-Chang Liu; Hua Xu; Xiao-Wen Wang (European Journal of Clinical Pharmacology, 2020)

Mercury exposure in sedentary and migratory Charadrius plovers distributed widely across China - Tongping Su; Xin Lin; Qin Huang; Demeng Jiang; Chi Zhang; Xuecong Zhang; Caroline Dingle; Eben Goodale; Pinjia Que; Rui Wang; Yang Liu (Environmental Science and Pollution Research, 2020)

The roles of tropical and subtropical wind stress anomalies in the El Niño Modoki onset - Xin Wang; Chengyang Guan; Rui Xin Huang; Wei Tan; Lei Wang (Climate Dynamics, 2019)

Geostrophic Spirals Generated by the Horizontal Diffusion of Vortex Stretching in the Yellow Sea - Xiangzhou Song; Rui Xin Huang; Dexing Wu; Fangli Qiao; Guansuo Wang (Advances in Atmospheric Sciences, 2019)

Lappaconitine, a C18-diterpenoid alkaloid, exhibits antihypersensitivity in chronic pain through stimulation of spinal dynorphin A expression - Ming-Li Sun; Jun-Ping Ao; Yi-Rui Wang; Qian Huang; Teng-Fei Li; Xin-Yan Li; Yong-Xiang Wang (Psychopharmacology, 2018)

Use of cationic microbubbles targeted to P-selectin to improve ultrasound-mediated gene transfection of hVEGF165 to the ischemic myocardium - Wei-hui Shentu; Cao-xin Yan; Chun-mei Liu; Rui-xiang Qi; Yao Wang; Zhao-xu Huang; Li-ming Zhou; Xiang-dong You (Journal of Zhejiang University-SCIENCE B, 2018)

Transformations of 2-line ferrihydrite and its effect on cadmium adsorption - Yi Huang; Shipeng Zhang; Chao Liu; Huilin Lu; Shijun Ni; Xin Cheng; Zhijie Long; Rui Wang (Environmental Science and Pollution Research, 2018)

Inhibition of P2X7 Receptor Ameliorates Nuclear Factor-Kappa B Mediated Neuroinflammation Induced by Status Epilepticus in Rat Hippocampus - Cheng Huang; Xiao-sa Chi; Rui Li; Xin Hu; Hai-xia Xu; Jin-mei Li; Dong Zhou (Journal of Molecular Neuroscience, 2017)

Abnormal O-GlcNAcylation of Pax3 Occurring from Hyperglycemia-Induced Neural Tube Defects Is Ameliorated by Carnosine But Not Folic Acid in Chicken Embryos - Rui-Rong Tan; Yi-Fang Li; Shi-Jie Zhang; Wen-Shan Huang; Bun Tsoi; Dan Hu; Xin Wan; Xuesong Yang; Qi Wang; Hiroshi Kurihara; Rong-Rong He (Molecular Neurobiology, 2017)

Molecular cloning and characterization of α-amylase/subtilisin inhibitor from rhizome of Ligusticum chuanxiong - Ji-hua Yu; Yang-yang Li; Mian Xiang; Jian-quan Zhu; Xin-he Huang; Wan-Jun Wang; Rui Tan; Jia-yu Zhou; Hai Liao (Biotechnology Letters, 2017)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Heaving modes in the world oceans - Rui Xin Huang (Climate Dynamics, 2015)

Molecular cloning and characterization of caffeic acid 3-O-methyltransferase from the rhizome of Ligusticum chuanxiong - Juan-Juan Li; Gan Zhang; Ji-hua Yu; Yang-yang Li; Xin-he Huang; Wan-Jun Wang; Rui Tan; Jia-yu Zhou; Hai Liao (Biotechnology Letters, 2015)

Scientific questions about South China Sea ocean dynamics - Rui Xin Huang; Yan Du (Acta Oceanologica Sinica, 2015)

Zonal overturning circulation and heat flux induced by heaving modes in the world oceans - Wei Tan; Rui Xin Huang; Weiqiang Wang; Xin Wang (Acta Oceanologica Sinica, 2015)

Rhodococcus agglutinans sp. nov., an actinobacterium isolated from a soil sample - Qian-Qian Guo; Hong Ming; Xiao-Ling Meng; Yan-Yan Duan; Rui Gao; Jian-Xin Zhang; Jian-Rong Huang; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2015)

Brittleness index and seismic rock physics model for anisotropic tight-oil sandstone reservoirs - Xin-Rui Huang; Jian-Ping Huang; Zhen-Chun Li; Qin-Yong Yang; Qi-Xing Sun; Wei Cui (Applied Geophysics, 2015)

Energetics of lateral eddy diffusion/advection: Part IV. Energetics of diffusion/advection in sigma coordinates and other coordinates - Rui Xin Huang (Acta Oceanologica Sinica, 2014)

Energetics of lateral eddy diffusion/advection: Part III. Energetics of horizontal and isopycnal diffusion/advection - Rui Xin Huang (Acta Oceanologica Sinica, 2014)

Energetics of lateral eddy diffusion/advection: Part II. Numerical diffusion/diffusivity and gravitational potential energy change due to isopycnal diffusion - Rui Xin Huang (Acta Oceanologica Sinica, 2014)

Energetics of lateral eddy diffusion/advection: Part I. Thermodynamics and energetics of vertical eddy diffusion - Rui Xin Huang (Acta Oceanologica Sinica, 2014)

Constructing genetic linkage maps for Pinus elliottii var. elliottii and Pinus caribaea var. hondurensis using SRAP, SSR, EST and ISSR markers - Hui-xiao Yang; Rui Luo; Fen-cheng Zhao; Tian-yi Liu; Chun-xin Liu; Shao-wei Huang (Trees, 2013)

WHAMM is required for meiotic spindle migration and asymmetric cytokinesis in mouse oocytes - Xin Huang; Lu Ding; Rui Pan; Peng-Fei Ma; Pan-Pan Cheng; Chun-Hui Zhang; Yu-Ting Shen; Lin Xu; Yu Liu; Xiao-Qin He; Zhong-Quan Qi; Hai-Long Wang (Histochemistry and Cell Biology, 2013)

Spatio-temporal reconstruction of air temperature maps and their application to estimate rice growing season heat accumulation using multi-temporal MODIS data - Li-wen Zhang; Jing-feng Huang; Rui-fang Guo; Xin-xing Li; Wen-bo Sun; Xiu-zhen Wang (Journal of Zhejiang University-SCIENCE B, 2013)

A new bioorganic fertilizer can effectively control banana wilt by strong colonization with Bacillus subtilis N11 - Nan Zhang; Kai Wu; Xin He; Shu-qing Li; Zhen-hua Zhang; Biao Shen; Xing-ming Yang; Rui-fu Zhang; Qi-wei Huang; Qi-rong Shen (Plant and Soil, 2011)

The role of diurnal cycle in subduction/obduction - Ling Ling Liu; Rui Xin Huang; Fan Wang (Journal of Oceanography, 2011)

Estimate of eddy energy generation/dissipation rate in the world ocean from altimetry data - Chi Xu; Xiao-Dong Shang; Rui Xin Huang (Ocean Dynamics, 2011)

The effects of flooding on several hybrid poplar clones in Northern China - Ji-Rui Gong; Xin-Shi Zhang; Yong-Mei Huang; Chun-Lai Zhang (Agroforestry Systems, 2007)